(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Dermestes maculatus is a major pest of stored fish in Nigeria, fish is preserved with highly persistent synthetic chemicals. There have been an increasing effort at developing plant-based toxicants that are environmentally friendly. Therefore, this study was conducted to screen the leaf extract of Azadirachta indica for phytochemical constituents. The efficacy of the methanolic leaf extract of the plant against D. maculatus was also evaluated. The leaves of A. indica were obtained, processed and taken to laboratory for methanolic extraction. Phytochemical screening was carried out to identify saponins, flavonoids, alkaloids, tannins, steroids, cardiac glycosides, glycosides, triterpenes and carbohydrates using standard procedure. Both clean and infested samples of smoke-dried Clarias gariepinus were purchased from Sabon Gari Market, Zaria. The infested samples were used as initial source of D. maculatus larvae. Range finding test was carried out prior to the bioassay. During the bioassay, clean un-infested fish samples were weighed and introduced into kilner jars and respective dosages of 0.2g, 0.4g, 0.6g and 0.8g of extract were added. Another set of fish samples without the extract were maintained as control. The experiment was arranged in Completely Randomized Design with three replicates. Fifteen larvae of D. maculatus were introduced into both treated and control containers and covered. Mortality was recorded after 24, 48, 72 and 96 hours. Data obtained revealed an increase in mortality with increasing dose and time. Mortality ranged from 1.67 to 11.00. Therefore, leaf extract of A. indica should be incorporated in the development of larvicide against D. maculatus.